The Role of Compensation and Work Discipline in Enhancing Employee Performance in Public Utility Organizations: Empirical Evidence from Medan City - Nichita Nichita; Delvis Stevhen Sihombing; Miquel Carlos Silalahi; Anton Luvi Siahaan; Herlina Novita (SEAN Institute, 2026)
This study investigates the influence of compensation and work discipline on employee performance in PUD Kota Medan, a public utility organization in Indonesia. Grounded in human resource management theory, the study adopts a quantitative research design using a descriptive survey approach. The population comprised all employees of PUD Kota Medan, with a sample of 40 respondents selected through simple random sampling. Data were collected using a structured questionnaire measured on a Likert scale. The data were analyzed using validity and reliability testing, classical assumption diagnostics, and multiple linear regression analysis, supported by t-test, F-test, and coefficient of determination using SPSS 24. The empirical results indicate that compensation has a positive and statistically significant effect on employee performance (t = 3.459; p < 0.05). Similarly, work discipline also demonstrates a positive and significant effect on employee performance (t = 5.857; p < 0.05). Furthermore, the simultaneous effect of compensation and work discipline on employee performance is statistically significant (F = 107.286; p < 0.001). The coefficient of determination (R² = 0.845) reveals that 84.5% of the variation in employee performance is explained by compensation and work discipline, while the remaining 15.5% is influenced by other unobserved factors. The findings suggest that the implementation of fair compensation systems and strong disciplinary mechanisms plays a crucial role in improving employee performance within public sector organizations. This study contributes to the existing literature on human resource management by providing empirical evidence from a municipal utility context in a developing economy.